Virtual crossmatch and calculated panel reactive antibody: two sides of the same coin - Lima, Bruno A. (2015)
Background: The demand for kidneys for transplantation grows daily due to the successful treatment of many patients with end stage renal disease. The success of kidney transplants depends largely on genetic and immunological compatibility between the organ and its recipient. An important barrier to kidney transplantation is the sensitization of transplant candidates to human leukocyte antigen (HLA).